2018
DOI: 10.6018/analesps.34.3.319211
|View full text |Cite
|
Sign up to set email alerts
|

Evidencias psicométricas sobre la validez y fiabilidad del cuestionario de capital psicológico (PCQ-12) en población mexicana

Abstract: El capital psicológico es un constructo que se incluye en el marco de comportamiento organizacional positivo, que se basa en principios positivos de psicología. Este concepto está compuesto por cuatro dimensiones interrelacionadas: autoeficacia, esperanza, resiliencia y optimismo. El objetivo de este estudio fue reportar las propiedades psicométricas de una de las medidas de capital psicológico, el Cuestionario de Capital Psicológico-12 (PCQ-12), en una muestra de 396 trabajadores mexicanos. La estructura del … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
12
0
4
Order By: Relevance
“…The low reliability value (α = 0.65) observed in our study is also found in other studies that used the PCQ-12. Dawkins et al [64] observed in a review of 29 psychometric studies that optimism and resilience dimensions tend to be lower than the self-efficacy and hope dimensions [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low reliability value (α = 0.65) observed in our study is also found in other studies that used the PCQ-12. Dawkins et al [64] observed in a review of 29 psychometric studies that optimism and resilience dimensions tend to be lower than the self-efficacy and hope dimensions [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…The malleability of psychological capital is explained by social cognitive theory, self-efficacy, and the human agency theory of Bandura [66,73]. Human agency is the ability to exercise control over our own functioning and over the events that affect our lives [73].…”
Section: Implications For Promoting Well-being and Sustainability In mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, each of the dimensions has a reliability coefficient of 0.605 (hope), 0.766 (efficacy), 0.650 (resilience), and 0.359 (optimism). For the dimension of optimism, it happens to have a low level of reliability coefficient, but as proven in the research of Santana-Cárdenas, Viseu, López-Núñez, and Jesús (2018) [12] who also used the PCQ-12, it showed a Cronbach Alpha of 0.81 in all models tested in the study. Based on this statement, this measuring tool remains reliable based on the principle of external validity.…”
Section: Scale Of Psychological Capitalmentioning
confidence: 77%
“…However, some studies found that a four-factor structure fits better than the second-order model (e.g. López-Núñez et al, 2018;Santana-Cárdenas et al, 2018;Viseu et al, 2012). This controversy appears largely in the adaptations of the scale in Portugal and Spain, which could indicate an effect related to the context or translation (Djourova et al, 2019).…”
mentioning
confidence: 99%